2019
DOI: 10.3390/molecules24030473
|View full text |Cite
|
Sign up to set email alerts
|

Ripe and Raw Pu-Erh Tea: LC-MS Profiling, Antioxidant Capacity and Enzyme Inhibition Activities of Aqueous and Hydro-Alcoholic Extracts

Abstract: Herein, we reported a detailed profiling of soluble components of two fermented varieties of Chinese green tea, namely raw and ripe pu-erh. The identification and quantification of the main components was carried out by means of mass spectrometry and UV spectroscopy, after chromatographic separation. The antioxidant capacity towards different radical species, the anti-microbial and the enzyme inhibition activities of the extracts were then correlated to their main constituents. Despite a superimposable qualita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…The collagenase enzyme inhibits the retention of skin elasticity and tensile strength [ 82 ]. Indeed, different studies have shown the importance of natural antioxidants due to their efficacy in delaying the premature aging through the inhibition of collagenase activity [ 78 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The collagenase enzyme inhibits the retention of skin elasticity and tensile strength [ 82 ]. Indeed, different studies have shown the importance of natural antioxidants due to their efficacy in delaying the premature aging through the inhibition of collagenase activity [ 78 , 83 ].…”
Section: Resultsmentioning
confidence: 99%
“…The collagenase inhibitory assay was performed similarly to those described by Roda et al [ 83 ], using a Collagenase Activity Assay Kit (Sigma-Aldrich ® ). This kit measures the collagenase activity with a synthetic peptide (i.e., FALGPA; N-(3-[2-Furyl]acryloyl)-Leu-Gly-Pro-Ala) that mimics the collagen structure.…”
Section: Methodsmentioning
confidence: 99%
“…The decreased soluble sugar content may be a result of the proliferation of microorganisms, which leads to the decomposition of soluble carbohydrates. It is also possible that soluble sugars react with amino acids in the Maillard reaction as described previously 37 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Pu‐erh ripe tea has been become the main research object of tea (Chen et al., 2016; Roda et al., 2019; Valentino et al., 2020; Zhang et al., 2019b). As to Pu‐erh raw tea, the researchers are rarely and mainly focus on its pharmacological activities or performances.…”
Section: Introductionmentioning
confidence: 99%
“…assamica Kitamura, which is planted in southwestern China (Liu et al., 2018). It is generally divided into Pu‐erh raw tea, Pu‐erh aging tea, and Pu‐erh ripe tea deriving from the manufactured process techniques and time‐consumption (Roda et al., 2019). Pu‐erh raw tea is produced by “fixation” after being picked, and it is fermented for several months to produce Pu‐erh ripe tea on the condition of microorganisms.…”
Section: Introductionmentioning
confidence: 99%